Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x-1+1-1+1-1\right)=0\)
\(x=0+1-1+1-1\)
\(x=0\)
chúc bn học tốt!
hihi@__@
1) ( y-25):4 - 120 = 0 2) 120 - ( x+25 )x4 = 0
( y-25 ):4 = 0+120 (x+25) x4 =120-0
( y-25):4 =120 (x+25) x4 =120
( y-25)=120x4 (x+25)=120:4
y-25=480 x+25=30
y=480+25 x=30-25
y=505 x=5
k mk nha
-x-1+x-4+3-x=0
(-x+x-x)+(-1-4+3)=0
-x-2=0
-x=2
x=-2
M = 126 x ( a x 1 - a : 1 ) x a x 26
M = 126 x 0 x a x 26
M = 0 x a x 26
M = 0
1x0=0
1 x 0 = 0
Mọi số nhân với 0 đều bằng 0